Religious Rituals and Cultural Identity in: Leila Aboulela’s Minaret (2005) - Zeboudj ,Zineb; Zeghad ,Nour el houda; Boumous, Moufida (Faculty of Letters and Foreign Languages Department of English, 2017)
Leila Aboulela‘s Minaret (2005) engages with the Muslim African immigrant experience in Britain. This dissertation is about religious rituals and cultural identity in this novel. It draws on the first chapter to present the theoretical framework of Aboulela’s literature in general and Minaret in specific. While the second and third chapters are about the analytic part of the novel in relation to the role of religion, more specifically Islam, culture and traditions in re-shaping the life of the novel’s protagonist. In order to depict the features above, we decided to adopt the analytical method. The objectives behind this dissertation are first, to reach the conclusion that Aboulela’s Minaret is religiously rich. Second, to prove that Islam transmitted the life of the main character to a better status. Motives behind conducting this research are to show that Muslims in a Western atmosphere are able to keep their Islamic and cultural identities alive, so they present Islam properly.